탄광부 진폐증과 용접공 폐증에 있어 흉부-X선 소견과 폐기능의 비교 - 박동열; Dong Youl Park; 황주호; Joo Ho Hwang; 강병선; Byung Son Kang; 정찬수; Chan Su Chung; 김화조; Wha Jo Kim (Tuberculosis and respiratory diseases, 1995)
Background: Chest X-ray of coal workers' pneumoconiosis and shipyard welders' lung show similar and regular opacities mostly, it is very difficult that we distinguish the former from the latter by only chest X-ray. so we performed this study to understand the progression of the disease and to provide the disease by considering pulmonary function and other factors in proportion to the profusion of small regular opacities of chest X-ray in both groups. Method: 430 coal workers' pneumoconiosis were compared with 311 shipyard welders' lung by the number, the age, the duration of dust exposure, %vital capacity(%VC), %FEV1.0, the type of ventilatory impairment, the combined pulmonary disease according to the profusion of small regular opacities on the chest radiographs, which were classified into category 0/1, category 1, and category 2. Result: 1) the percent of category 2 in coal workers' pneumoconiosis was 54.4%. the percent of category 1, and category 2 in welders' lung were 60.0%, 7.4%. the progression to the category 2 was higher in coal workers' pneumoconiosis than in welders' lung 2) The mean age was higher in coal workers' pneumoconiosis than in welders' lung, significantly increased in proportion to the progresion of profusion of small regular opacities in both groups 3) There was no difference in the duration of dust exposure by category 1/0, but the duration of dust exposure by category 1, 2 in coal workers' pneumoconiosis more significantly increased than in welders' lung. the duration in the proportion of category 2 to category 0/1, 1 significantly increased in the proportion to small regular opacities in coal workers' pneumoconiosis. but there was no significant difference in the proportion to small regular opacities in duration of dust exposure in welders' lung. 4) There was no significant difference of mean values of %VC(%vital capacity)in both groups except for category 1. the mean values of %VC had no relationship between the progression of small regular opacities in both groups. 5) The mean values of %FEV1.0 decreased more significantly in coal workers' pneumoconiosis than in welders' lung except for category 0/1. and decreased significantly in proportion to the profusion of small regular opacities in coal workers' pneumoconiosis. there was significant difference of %FEV1.0 in the proportion of category 2 to category 011 in welders' lung. 6) there were no significant difference of %FEV1.0, %VC in smoker and nonsmoker in both groups. 7) With regard to the type of ventilation in both groups in coal workers' pneumoconiosis 21.4 percent of patients belonged to the restrictive type, 11.6 percent to the obstructive type, 5.6 percent to the combined type, but in welders' lung 21.8 percent to the restrictive type, 2.9 percent to the obstructive type, 1.9 percent to the combined type. 8. in the pulmonary disease, the incidence of the pulmonary tuberculosis was the most in both groups, was more in coal workers' pneumoconiosis than welders' lung Conclusion: If we compare coal workers' pneumoconiosis with electric arc welders'lung by considering pulmonary function and other factors in proportion to the profusion of chest X-ray, I think that we will have the better result in understanding the progression of the disease and provision of the disease in both groups. 연구 배경: 탄광부 전폐증과 조선소 용접공 폐증의 흉부 X-선 소견은 유사한 규칙성 음영을 보이는 예가 대부분이지만 이를 흉부 X-선만으로 구별한다는 것은 극히 어려운 일이다. 본 연구는 탄광부 진폐증과 용접공 폐증의 흉부 X-선 소견에 따른 폐기능과 다른 요인들을 비교하여 두 질환의 진행과정과 그것에 대한 대책에 도움을 주고져 한다. 방법: 탄광부 진폐증 430명과 용접공 폐증 311명을 대상으로 흉부 X-선 소견에서 소원형 음영의 조밀도에 따라 진폐의증, 1형, 2형으로 나누어 분포, 나이, 분진의 노출기간, %폐활량, 1초율 및 환기장해의 행태, 동반된 폐질환 등을 서로 비교하였다. 1) 탄광부 진폐증에서는 2형이 54.1%로 가장 많았고 용접공 폐증에서는 1형이 55.95%, 2형이 7.4%로 탄광부 진폐증에서 2형으로 진행도가 높았다. 2) 평균연령은 용접공 폐증에 비해 탄광부 폐증에서 유의하게 높았고, 소원형 음영의 조밀도가 증가함에 띠라 탄광부 폐증과 용접공 폐증에서 유의한 증가를 보였다. 3) 분진 노출의 기간은 진폐의증에서는 유의한 차이가 없었으나, 1형과 2형의 탄광부 폐증에서 유의한 증가를 보였고, 소원형 음영의 조밀도가 증가됨에 따라 탄광부 폐증에서는 2형이 진폐의증과 1형보다 유의하게 증가하였으나, 용접공 폐증에서는 유의한 차이가 없었다. 4) %폐활량은 1형을 제외하고는 탄광부 폐증과 용접공 폐증에서 유의한 차이가 없었고, 소원형 음영의 조밀도에 따라서도 두 그룹에서 일정한 경향이 없었다. 5) 1초율은 진폐의증을 제외하고는 1형과 2형에서 탄광부 폐증에서 유의하게 감소하였고, 소원형 음영의 증가에 따라 탄광부 폐증에서는 유의한 감소를 보였으나 용접공 폐증에서는 진폐의증에 비해 2형에서만 유의하게 감소하였다. 6) 두 그룹에서 흡연과 비흡연에 따른 %VC, $%FEV_{1.0}$의 유의한 차이를 보이지 않았다. 7) 폐기능 장해의 유형에 따라 탄광부 폐증에서 구속형 상해가 21.4%, 폐색형 장해가 11.6%, 혼합형 상해가 5.6%이고, 용접공 폐증에서 구속형 장해가 21.8%, 폐색형 장해가 2.9%, 혼합형 장해가 1.9%를 보였고, 탄광부 폐증에서는 조밀도가 증가할 수 록 폐색형 장해는 증가하였다. 8) 두 그룹에서 폐결핵의 발병률이 가장 높았으며 용접공 폐증에서보다 탄광부 진폐증에서 높았다. 결론: 탄광부 진폐증과 용접공 폐증에서 흉부 X-선 소견과에 따른 폐기능 비롯한 다른 요인들을 비교하면 질병의 진행정도와 진행에 대한 대책에 도움을 줄 것으로 생각된다.